2019
DOI: 10.1093/sleep/zsz266
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and sleep/wake-dependent variations in tau phosphorylation are driven by temperature

Abstract: Study Objectives Aggregates of hyperphosphorylated tau protein are a hallmark of Alzheimer’s disease (AD) and other tauopathies. Sleep disturbances are common in AD patients, and insufficient sleep may be a risk factor for AD. Recent evidence suggests that tau phosphorylation is dysregulated by sleep disturbances in mice. However, the physiological regulation of tau phosphorylation during the sleep–wake cycle is currently unknown. We thus aimed to determine whether tau phosphorylation is regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 81 publications
1
28
0
Order By: Relevance
“…These notably included Ser 202/Thr 205 [36,37,42], used for Braak staging [5] and to characterize MK6420 uptake in post mortem audioradiography [73], as well as other phosphosites found to be hyperphosphorylated in AD, including Thr 181 [42,47], relevant to CSF and plasma P-tau. A temperature decrease of 37.4°C to 36.3°C also robustly increased human neuronal tau phosphorylation at these phosphosites in vitro [47]. Additional temperature-dependent molecular processes involved in tau proteostasis may also link lower Tb to tau aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These notably included Ser 202/Thr 205 [36,37,42], used for Braak staging [5] and to characterize MK6420 uptake in post mortem audioradiography [73], as well as other phosphosites found to be hyperphosphorylated in AD, including Thr 181 [42,47], relevant to CSF and plasma P-tau. A temperature decrease of 37.4°C to 36.3°C also robustly increased human neuronal tau phosphorylation at these phosphosites in vitro [47]. Additional temperature-dependent molecular processes involved in tau proteostasis may also link lower Tb to tau aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Planel et al, Arendt et al, and others showed in an elegant series of rodent experiments made over the last 20 years that a small (< 1°C) decrease in body temperature (Tb) within the human physiological range substantially increases neuronal tau phosphorylation-notably at phosphosites that are hyperphosphorylated in AD patients [36][37][38][39][40][41]. This effect was induced by experimental Tb decrease [36,37,42], seasonal torpor [43,44], as well as sleep-associated Tb decrease, which drove a robust increase in tau phosphorylation compared to waking in wild-type mouse [45]. Regarding the underlying mechanism, Tb decrease inhibited the activity of the major tau phosphatase (PP2A) more so than tau kinase activity, resulting in a net phosphorylation increase [36,46].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations